New tithonian biostratigraphic data from the Neuquén Basin, Argentine Andes: a contribution from the southern hemisphere - Lescano, Marina Aurora (2022)
We present new biostratigraphic data provided by ammonites, calcareous nannofossils, and calpionellids from Las Alcantarillas, a 127 m-thick section from the Neuquén Basin, western Argentina. The combined biostratigraphic information of these fossil groups enables to accurately correlate our findings from the Andes with the current Tithonian biozones-scheme of the Western Mediterranean Province of theTethyan Realm. The biostratighaphic records show that the early Tithonian calcareous nannofossil NJT 15 Zone correlates with the early Tithonian V. andesensis, P. zitteli, A. proximus, and W. internispinosum ammonite Zones, while its upper part correlates with the Chitinoidella calpionellid Zone. In the studied section, the lower/upper Tithonian boundary is defined by the base of the Crassicollaria calpionellid Zone, which is close to the base of the NJT 16 nannofossil Zone and to the base of the upper Tithonian Corongoceras alternans ammonite Zone. Levels assigned to the NJT17 nannofossil Zone (upper Tithonian) are recognized and correlated with the upper part of the Crassicollaria calpionellid Zone and with the Substeueroceras koeneni ammonite Zone. So far, it has not been possible to define accurately the Jurassic/Cretaceous boundary in Las Alcantarillas. However, in the upper levels of the section, the Argentiniceras noduliferum and the Spiticeras damesi ammonite Zones, traditionally assigned to the Berriasian, have been identified. In addition to the paleontological analyses, bulk-rocks were sampled every 6 cm to measure magnetic susceptibility and δ13Corg, and tuff layers were sampled to obtain precise absolute ages on U-Pb zircons. An astrochronological framework has been obtained from the spectral analyses on magnetic susceptibility, which was integrated to the radiochronology results from the zircons. The high-resolution (every ~20 ka) δ 13Corg curve, the first of its kind obtained in the Neuquén Basin, will help in the global correlation of the Andean Late Jurassic and add a new perspective in the understanding of the stratigraphic distribution of its fossil associations.